METODE BERTIPE NEWTON UNTUK AKAR GANDA DENGAN KONVERGENSI KUBIK - Risvi Ayu Imtihana; Imran M.; Asmara Karma (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses a Newton-type method for multiple roots, which is derived using a linear combination of Newton’s method for multiple roots and an iterative method derived based on a quadrature Gauss-type. Analytic studies show that this iterative method has a third order of convergence and for each iteration, it requires function evaluations three times, so that the efficiency index of the method is 1.44225. Furthermore, computational tests show that the method is superior to other mentioned methods, in terms of the number of iterations required to obtain the roots.